2021
DOI: 10.3389/fnagi.2021.607988
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Aging Alters the Functional Connectivity of Creative Cognition in the Default Mode Network and Cerebellar Network

Abstract: Creativity is a higher-order neurocognitive process that produces unusual and unique thoughts. Behavioral and neuroimaging studies of younger adults have revealed that creative performance is the product of dynamic and spontaneous processes involving multiple cognitive functions and interactions between large-scale brain networks, including the default mode network (DMN), fronto-parietal executive control network (ECN), and salience network (SN). In this resting-state functional magnetic resonance imaging (rs-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 121 publications
2
9
0
Order By: Relevance
“…Furthermore, a spatial‐to‐template match was used to obtain the various resting‐state brain networks. Our selection of the number of components was consistent with our previous work reported on the network neuroscience of aging (Patil et al, 2021).…”
Section: Methodssupporting
confidence: 77%
See 3 more Smart Citations
“…Furthermore, a spatial‐to‐template match was used to obtain the various resting‐state brain networks. Our selection of the number of components was consistent with our previous work reported on the network neuroscience of aging (Patil et al, 2021).…”
Section: Methodssupporting
confidence: 77%
“…The group‐ICA was first performed on rs‐fMRI data to reveal major brain networks across age groups (Patil et al, 2021). Eleven resting‐state brain networks from 30 ICA components were then obtained, which is consistent with our previous work that identified age‐invariant resting‐state networks (Patil et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While divergent ability was not significantly different between the two cohorts, functional connectivity between default and executive control networks was stronger and more extensive in older individuals (Adnan, Beaty, Silvia, et al, 2019). Further, more recent evidence demonstrated that higher resting state functional connectivity between default and executive control networks was positively associated with self-reported lifetime creative achievements in older adults, whereas connectivity in predominantly frontal, executive control regions was correlated with creative achievements in younger adults (Patil et al, 2021). Collectively, these are important findings suggesting that although aging appears to alter neural substrates of creative cognition, such changes may not negatively impact task performance.…”
Section: The Cognitive Psychology and Neuroscience Of Creativity In A...mentioning
confidence: 99%